Pengaruh Bencana Banjir Terhadap Pembayaran Pajak Kendaraan Bermotor (PKB) Di Kota Padang Provinsi Sumatera Barat - Derry Arya Pratama; Ary Subiyantoro; Prihartanto Eko Wibowo (LPPM AKADEMI MANAJEMEN ADMINISTRASI YOGYAKARTA, 2026)
This study aims to determine the effect of flood disasters on the payment of Motor Vehicle Tax (PKB) in Padang City and to assess the extent of the impact. The research employed a quantitative method, with data collected through questionnaires, observations, and literature review. The research sample consisted of 100 respondents, determined using the Slovin formula, while data analysis was conducted using validity and reliability tests, t-test, coefficient of determination, and simple linear regression. The results indicate that flood disasters have a significant effect on the payment of Motor Vehicle Tax (PKB) in Padang City. This is evidenced by the calculated t-value of 2.657, which is greater than the t-table value of 1.660, as well as a significance value of 0.000 < 0.05. The coefficient of determination results show an R Square value of 0.258, or 25.8%, meaning that flood disasters contribute 25.8% to the variation in Motor Vehicle Tax (PKB) payments, while the remaining 74.2% is influenced by other factors outside the scope of this study. The conclusion of this study is that flood disasters have a significant effect on the payment of Motor Vehicle Tax (PKB) in Padang City. Therefore, the local government and the Samsat office are expected to implement adaptive policies and provide more effective services for communities affected by flooding.